1973
DOI: 10.1136/bmj.4.5886.197
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors in Open Myelomeningocele with Special Reference to Sensory Level

Abstract: A total of 113 cases of open myelomeningocele operated on shortly after birth were followed up and the 80 survivors (71%) were assessed one and a quarter to seven and a half years later. Their disability was classified in terms of mobility, intelligence, continence, and major complications; these when combined provided an assessment of overall disability. The overall disability of the survivors was minimal in 6%, moderate in 40%, severe in 39%, and very severe in 15%.A number of clinical features present at bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 3 publications
2
42
0
Order By: Relevance
“…17 Sensory level was used as it was found to relate more closely to outcome in terms of mortality and disability than motor or external level, and remained stable over time. 17 It ranged from T5 in the severest cases to no sensory loss in the mildest.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Sensory level was used as it was found to relate more closely to outcome in terms of mortality and disability than motor or external level, and remained stable over time. 17 It ranged from T5 in the severest cases to no sensory loss in the mildest.…”
Section: Methods Participantsmentioning
confidence: 99%
“…The cohort of 117 consecutive individuals born with open spina bifida has previously been reviewed six times, with no loss to follow-up. [17][18][19][20][21] The aim of this review, conducted in 2007, was to investigate survival and causes of death in a complete and unselected cohort of open spina bifida at the mean age of 40 years.…”
mentioning
confidence: 99%
“…Also, the functional levels are mostly located within the lesion area and do not regularly coincide with the radiologic (skeletal) or with the anatomical (skin) defect. Similar observations are cited in the literature [13,[20][21][22][23][24]. For instance, Hunt et al [13,23] found the sensory level present at birth being the best predictive factor for long-term outcome in terms of mobility, continence, and overall disability rather than radiologic (skeletal), cutaneous, or motor activity level at birth.…”
Section: Discussionmentioning
confidence: 50%
“…Similar observations are cited in the literature [13,[20][21][22][23][24]. For instance, Hunt et al [13,23] found the sensory level present at birth being the best predictive factor for long-term outcome in terms of mobility, continence, and overall disability rather than radiologic (skeletal), cutaneous, or motor activity level at birth. In contrast, other authors found that the anatomical level obtained by prenatal ultrasound was the best predictive factor rather than radiographic or neuromotor levels found at birth [20,21,24].…”
Section: Discussionmentioning
confidence: 50%
“…Prov ided intact overlying skin is preserved and further neurologic deteriora tion does not occur, it is of common practice to advise excision of the sac and repair of the spinal defect within the range of 3-6 months of age [2,6,9. 10], particularly in cases of sacral location where paralysis of lower limbs is minimal.…”
Section: Discussionmentioning
confidence: 99%